If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(1 + -2v) = 11 + -9v (1 * 5 + -2v * 5) = 11 + -9v (5 + -10v) = 11 + -9v Solving 5 + -10v = 11 + -9v Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '9v' to each side of the equation. 5 + -10v + 9v = 11 + -9v + 9v Combine like terms: -10v + 9v = -1v 5 + -1v = 11 + -9v + 9v Combine like terms: -9v + 9v = 0 5 + -1v = 11 + 0 5 + -1v = 11 Add '-5' to each side of the equation. 5 + -5 + -1v = 11 + -5 Combine like terms: 5 + -5 = 0 0 + -1v = 11 + -5 -1v = 11 + -5 Combine like terms: 11 + -5 = 6 -1v = 6 Divide each side by '-1'. v = -6 Simplifying v = -6
| 6(8+4n)=-3+7n | | -5(-8-5x)=-28+8x | | (5+4j)-(x+yi)=(-1-3i) | | 13q-12q=15 | | -8h-3=3-10h | | 6x-1y=-8 | | 5x-20=-2+8k | | -5(6k+7)=k-4 | | 9g+12g+-18g=-18 | | 2d=-18 | | 3(x-7)=5(x+1) | | P/5=-12 | | 3s^2+s-2=0 | | -8x+19+9x+22=2 | | 17c+c-16c-c=20 | | 4x+6=-x-4 | | A-16=-30 | | 7x+8(x+10)=26+9x | | 16h+14h+-10h-5h-14h=-3 | | 7+43.2m=1.23 | | 4n-9-6n=-31 | | 5c-4c=7 | | 6(1-10n)=6+9n | | 18+5x=6(x+2)-3x | | 12x+51=2 | | 10.5n=73.5 | | 5-x=30-20 | | 80c=8 | | -t-15t+17t=-17 | | 40+4.50x=112 | | 88=22j | | 9x/12=36 |